Strain improvement and up scaling of phytase production by aspergillus niger NCIM 563 under submerged fermentation conditions - Shah, P.; Bhavsar, Kavita P.; Soni, S. K.; Khire, Jayant Malhar (Journal of Industrial Microbiology & Biotechnology, 2009)
Combination of physical and chemical mutagenesis was used to isolate hyper secretory strains of Aspergillus niger NCIM 563 for phytase production. Phytase activity of mutant N-1 and N-79 was about 17 and 47% higher than the parent strain. In shake flask the productivity of phytase in parent, mutant N-1 and N-79 was 6,181, 7,619 and 9,523 IU/L per day, respectively. Up scaling of the fermentation from shake flask to 3 and 14 L New Brunswick fermenter was studied. After optimizing various fermentation parameters like aeration, agitation and carbon source in fermentation medium the fermentation time to achieve highest phytase activity was reduced considerably from 14 days in shake flask to 8 days in 14 L fermenter. Highest phytase activity of 80 IU/ml was obtained in 1% rice bran-3.5% glucose containing medium with aeration 0.2 vvm and agitation 550 rpm at room temperature on 8th day of fermentation. Addition of either bavistin (0.1%), penicillin (0.1%), formalin (0.2%) and sodium chloride (10%) in fermented broth were effective in retaining 100% phytase activity for 8 days at room temperature while these reagents along with methanol (50%) and ethanol (50%) confer 100% stability of phytase activity at 4A degrees C till 20 days. Among various carriers used for application of phytase in feed, wheat bran and rice bran were superior to silica and calcium carbonate. Thermo stabilization studies indicate 100% protection of phytase activity in presence of 12% skim milk at 70A degrees C, which will be useful for its spray drying.
Keywords: Agriculture residue; Aspergillus niger; Phytase; phytate degradation; Poultry feed supplement; Submerged fermentation

Strain improvement of lactobacillus lactis for d-lactic acid production - Joshi, D. S.; Singhvi, M. S.; Khire, Jayant Malhar; Gokhale, D. V. (Biotechnology Letters, 2010)
Three mutants, isolated by repeated UV mutagenesis of Lactobacillus lactis NCIM 2368, produced increased d-lactic acid concentrations. These mutants were compared with the wild type using 100 g hydrolyzed cane sugar/l in the fermentation medium. One mutant, RM2-24, produced 81 g lactic acid/l which was over three times that of the wild type. The highest d-lactic acid (110 g/l) in batch fermentation was obtained with 150 g cane sugar/l with a 73% lactic acid yield. The mutant utilizes cellobiose efficiently, converting it into d-lactic acid suggesting the presence of cellobiase. Thus, this strain could be used to obtain d-lactic acid from cellulosic materials that are pre-hydrolyzed with cellulase.
Keywords: Cellobiose utilization; D-Lactic acid production; Lactobacillus lactis; Mutant; Sucrose (cane sugar)

Selection of phytase producing yeast strains for improved mineral mobilization and dephytinization of chickpea flour - Pable, A.; Gujar, P.; Khire, Jayant Malhar (Journal of Food Biochemistry, 2014)
Among 600 yeast isolates screened for phytase production, five (Zygosaccharomyces bisporusNCIM 3265 and 3296, Williopsis saturnusNCIM 3298, Zygosaccharomyces priorionusNCIM 3299 and Schizosaccharomyces octosporusNCIM 3297) were selected as potential phytase producers. Phytase activity was found to be cell wall associated with temperature and pH optima of 50C and 4.0, respectively. Highest phytase production was attained in cane juice medium as compared with other media used. Addition of phytase to chickpea flour significantly enhanced mineral mobilization by approximately 20-28%, 26-37% and 24-42% for Zn2+, Fe2+ and Ca2+, respectively, and decreased phytic acid content by about 75-88%.